Factors influencing the intention of women with perinatal depression and their spouses to seek professional psychological help: a cross-sectional latent profile analysis - Zou, Qinhan; Liu, Xianliang; Yang, Yingzi; Yang, Yuelai; Duan, Xia (Frontiers in Public Health, 2025)
BackgroundSeeking professional psychological help can improve outcomes for women with perinatal depression (PND). However, the use of professional psychological help-seeking behaviors for women with PND is not promising. Spouses are important sources of support and play a decision-making role in the process of seeking professional psychological help for women with PND. Exploring the factors that influence couples’ intention to seek professional psychological help is important for developing effective interventions. This study aims to investigate the level and latent profiles of intention to seek professional psychological help in women with PND and their spouses, and identify influencing factors associated with different profiles.MethodsA cross-sectional study involving 267 women with PND and 267 spouses was conducted. The General Help-Seeking Questionnaire-the Intention to Seek Professional Psychological Help (GHSQ-ISPH), the Questionnaire of Stigma for Seeking Professional Psychological Help Questionnaire, the Attitude Toward Seeking Professional Psychological Help Scale, the Self-Efficacy for Seeking Mental Health Care Help Scale and the Edinburgh Postnatal Depression Scale were used. Latent profile analysis was used to identify groups with similar levels of GHSQ-ISPH. Multiple logistic regression was used to explore influencing factors associated with the intention to seek professional psychological help.ResultsThe mean GHSQ-ISPH scores of women with PND and their spouses were 12.17 ± 4.06 and 12.61 ± 3.88, respectively. LPA yielded three profiles. The profiles were named based on the GHSQ-ISPH score to reflect the level to which women with PND and their spouses intend to seek professional psychological help: “Women low-Spouses high intention for help” (Profile 1), “Women high-Spouses low intention for help” (Profile 2) and “Couple high intention for help” (Profile 3). Multiple logistic regression showed that spouses with a monthly income (858-1285/USD), with lower openness to seeking treatment for emotional problems, lower knowledge competence beliefs, and negative attitudes toward seeking professional psychological help were significantly associated with Profile 2 than with Profile 3 (P < 0.05 or P < 0.001). PND women who received a university or college and with lower public stigma were more significantly related to Profile 1 than Profile 3 (P < 0.05).ConclusionThe findings of this study indicate a moderate level of intention to seek professional psychological help among women experiencing PND and their partners. These results offer valuable insights for perinatal nurses, suggesting the necessity for the development of targeted interventions aimed at enhancing couples’ intentions to pursue professional psychological support. Identifying the factors associated with each profile outlined in this research offers the opportunity for more personalized and effective interventions. Tailored approaches like these could substantially enhance engagement with mental health resources, leading to improved outcomes for couples affected during the perinatal period.